(untitled) (Al-Academy, 2020)
The theatrical show has gone through a lot of changes where the actor was the most significant factor in all the theatrical shows since the very beginning of the art of acting by the Greeks until the present day. The actor went through many stages that employed his tools in different ways. The body in the theatre had a great importance because it is the perceived physical element that creates the communication between the actor and the audience in the theatrical show. The actor’s body had a special language that carries different meanings and creates the communication between the actor and the audience in the theatrical show. The audience can decipher the codes of that body, thus, the researcher found the compatibility and difference in that language. Therefore, the title of the research has been the actor’s body language and its connotations in the Iraqi theatrical show. The study consists of four sections: (the methodological framework) consisting of the research problem, the need for it, its significance, objectives, and then the research terms have been identified. As for (the theoretical framework) it consists of two sections: the first section: the body and its language, references and their developments. The second section: the body language in the actor’s theatrical performance. The research procedures consist of the research community, method, sample, and tools and analyzing one sample which is (the naked) play. The study ends with the results, conclusions, suggestions, recommendations and a list of resources and references in addition to an abstract in English.